Detection of electromagnetic anomalies over seismic regions during two strong (MW > 5) earthquakes - Recchiuti, D.; D’Angelo, G.; Papini, E.; Diego, P.; Cicone, A.; Parmentier, A.; Ubertini, P.; Battiston, R.; Piersanti, M. (Frontiers in Earth Science, 2023)
Ionospheric disturbances (such as electromagnetic emissions) in connection to strong earthquakes have been reported in literature since over two decades. However, to be reliable, the identification of such disturbances would require a robust definition of the ionospheric background in absence of seismic activity and any other possible external input (e. g. solar activity). In this work, we present a new technique to evaluate the electromagnetic (EM) ionospheric background over seismic regions. We performed a multiscale statistical analysis of the ionospheric environmental background, using almost the entire CSES-01 (China Seismo-Electromagnetic Satellite) electric and magnetic field dataset (2019-2021). The result is a map of the averaged relative energy in a 6° x 6° latitude-longitude cell centered over the earthquake epicenter (EE), representing the ionospheric background. Only EM signal which statistically differs from the background should be considered as a potential event to be investigated. Finally, we present the results obtained for two strong earthquakes, the August 14, 2021 Haitian earthquake (7.2 MW ) and the September 27, 2021 Cretan (Greece) earthquake (6.0 MW ). For the first event a signal emerging from the background, characterized by a peculiar frequency ≃ 250 Hz has been identified. In the second event, the strong geomagnetic activity did not allow identifying any distinguishable signal from the background.